2017
DOI: 10.4103/jrms.jrms_728_16
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the ankle-brachial index by oscillometric blood pressure and automated ankle-brachial index

Abstract: Background:This study was conducted to assess the validity and reliability of ankle-brachial index (ABI) by oscillometric blood pressure (BP) measurement as compared with an automated ABI as a gold standard.Materials and Methods:This study was conducted at Golden Jubilee Medical Center, Thailand. All the data were collected from 303 patients at risk of peripheral arterial disease (PAD) who were 45 years of age or above and who underwent treatment at the outpatient medical clinic between June and December 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…A fourth issue relates to unsound investigative logic sometimes being employed. For example, Chongthawonsatid and Dutsadeevettakul (2017) assessed sensitivity, specificity, predictive values, and accuracy (Note 5) of the ABI by comparing results from one method of obtaining ABIs with another, the second of which they referred to as a "gold standard". In this situation, two highly similar screening tests were compared with each other and no diagnostic-level measure of PAD was involved.…”
Section: Issues Pertaining To Reference Standardsmentioning
confidence: 99%
“…A fourth issue relates to unsound investigative logic sometimes being employed. For example, Chongthawonsatid and Dutsadeevettakul (2017) assessed sensitivity, specificity, predictive values, and accuracy (Note 5) of the ABI by comparing results from one method of obtaining ABIs with another, the second of which they referred to as a "gold standard". In this situation, two highly similar screening tests were compared with each other and no diagnostic-level measure of PAD was involved.…”
Section: Issues Pertaining To Reference Standardsmentioning
confidence: 99%
“…Twenty-one papers were excluded based on the exclusion criteria (Fig. 1): 10 papers reported comparison of methods [26][27][28][29][30][31][32][33][34][35], five studies did not report measures of reliability [36][37][38][39][40], two studies compared raters' experience [41,42] and one reported a novel trial design, for which the reliability results were duplicated in another included paper [43]. One paper used measures repeated at up to 365 days apart, with a mean time between measures of 228 days, which is long enough to encompass changes attributable to progression of PAD [44].…”
Section: Resultsmentioning
confidence: 99%
“…3). Vascular compromise was further supported by ultrasound showing an ankle-brachial index [11] of 0.50 on the affected side compared with 1.66 on the right. Joint aspiration was negative for evidence of bacterial infection (no growth at 14 days; cell count not available because of cell debris), but serum Co and Cr levels were abnormally elevated.…”
Section: Case Historymentioning
confidence: 90%